2012
DOI: 10.1177/0956797612449177
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Roots of Environmental Attitudes

Abstract: Americans' attitudes about the environment are highly polarized, but it is unclear why this is the case. We conducted five studies to examine this issue. Studies 1a and 1b demonstrated that liberals, but not conservatives, view the environment in moral terms and that this tendency partially explains the relation between political ideology and environmental attitudes. Content analyses of newspaper op-eds (Study 2a) and public-service announcements (Study 2b) found that contemporary environmental discourse is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
634
10
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(691 citation statements)
references
References 35 publications
36
634
10
11
Order By: Relevance
“…Political conservatism is associated with a preference for the status quo (14), traditionalism (31), and a lesser reliance on harm and fairness principles in moral domains (32). Environmental protection (particularly in the context of proposed "solutions" to the problems created by climate change) typically challenges the economic status quo and tradition (10,17), and relies on harm/ fairness notions of morality (33). Hence any or all of these basic psychological factors might contribute to the present findings.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Political conservatism is associated with a preference for the status quo (14), traditionalism (31), and a lesser reliance on harm and fairness principles in moral domains (32). Environmental protection (particularly in the context of proposed "solutions" to the problems created by climate change) typically challenges the economic status quo and tradition (10,17), and relies on harm/ fairness notions of morality (33). Hence any or all of these basic psychological factors might contribute to the present findings.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, when only cost information was available to participants in study 2 (i.e., the blank-label conditions), there were no ideological differences in the selection of the energy-efficient option. Alternatively, there may be sources of political common ground with regard to the environment itself, because framing environmental protection in terms of psychological values that appeal to those on the political right (such as purity or patriotism) increases concern for the environment among political conservatives (17,33). Future research should identify whether tapping these less polarizing concerns, morals, and values can bridge the ideological gap in the willingness to pay for energy-efficient options.…”
Section: Discussionmentioning
confidence: 99%
“…For example Sheldon (2011) found that conservatives, who may be more likely to hold self-enhancing value orientations, were more supportive of environmental behavior when first asked to consider traditional US-American values. Feinberg and Willer (2013) found that conservatives were more environmentally concerned when the issue was framed around purity and sanctity instead of the harm/care moral framing typically used when discussing environmental issues. Perhaps, when debating real, local consequences of climate change, it will be necessary to include reminders of traditional conservative values or moral pleas framed to appeal to strong self-enhancing values.…”
Section: Values and Climate Impact Informationmentioning
confidence: 99%
“…It has even been argued that moral considerations are primary and shape our understanding of actions and events (Knobe 2007). It seems that environmental risks in particular are considered moral issues by many people (Böhm and Tanner 2013;Feinberg and Willer 2013;McDaniels, Axelrod, and Slovic 1995).…”
Section: Introductionmentioning
confidence: 99%